2016
DOI: 10.1017/s1431927616011739
|View full text |Cite
|
Sign up to set email alerts
|

Diplopods as Soil Bioindicators of Toxicity After Application of Residues From Sewage Treatment Plants and Ethanol Industry

Abstract: Residues like sewage sludge and vinasse have been reused as agricultural fertilizers, but they also present a potential to contaminate soils. Diplopods have been considered excellent bioindicators of soil contamination. In the present study, Rhinocricus padbergi were used to assess toxicity in samples of sewage sludge, biosolids, and sugarcane vinasse. The behavioral analysis, mortality rate, and histological, histochemical, and ultrastructural analyses of the midgut of diplopods were the parameters evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In general, in order to test the possible toxic effect, diplopods (e.g. Rhinocricus padbergi) have been considered excellent bioindicators of soil contamination (Christofoletti et al, 2016;Rastetter and Gerhardt, 2017). For instance, Christofoletti et al (2016) used Rhinocricus padbergi to assess toxicity in samples of BS.…”
Section: Possible Toxic Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, in order to test the possible toxic effect, diplopods (e.g. Rhinocricus padbergi) have been considered excellent bioindicators of soil contamination (Christofoletti et al, 2016;Rastetter and Gerhardt, 2017). For instance, Christofoletti et al (2016) used Rhinocricus padbergi to assess toxicity in samples of BS.…”
Section: Possible Toxic Effectsmentioning
confidence: 99%
“…Rhinocricus padbergi) have been considered excellent bioindicators of soil contamination (Christofoletti et al, 2016;Rastetter and Gerhardt, 2017). For instance, Christofoletti et al (2016) used Rhinocricus padbergi to assess toxicity in samples of BS. The behavioural analysis, mortality rate, and histological, histochemical, and ultrastructural analyses of the midgut of diplopods has been the parameters evaluated.…”
Section: Possible Toxic Effectsmentioning
confidence: 99%
“…Studies have been carried out mainly with sugar cane vinasse and several authors have concluded that this effluent can be toxic. Marinho et al (2014, Christofoletti et al (2016) and Correia et al (2017) observed its toxicity to different bioindicator organisms, such as fish, millipedes and Tradescantia pallida. There are no studies about the toxicity of orange vinasse, but Saverini et al (2012) analyzed the genotoxicity of citrus wastewater derived from the production of citrus juice and the extraction of essential oils in the Salmonella reversion assay (Ames test) and in V79 cells by Comet assay.…”
Section: Introductionmentioning
confidence: 99%
“…Some procedures can be used to form a biosolid that increases the solid content while decreasing the number of pathogenic microorganisms in the sewage sludge (Haynes et al 2009). However, studies by Christofoletti et al (2012Christofoletti et al ( , 2016 using the plant A. cepa and the millipede Rhinocricus padbergi as bioindicators showed the genotoxic and toxic potential of this residue, even after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the Brazilian millipede species R. padbergi in the evaluation of toxicity of complex substances was attested by several studies using different concentrations of vinasse (Christofoletti et al 2016), sewage sludge (Nogarol and Fontanetti 2010;Godoy and Fontanetti 2010;Perez and Fontanetti 2011;Bozzatto and Fontanetti 2012), landfarming soil originated from oil refinery (Souza and Fontanetti 2011), and the herbicide trifluralin (Merlini et al 2012). Thus, this organism proved to be an excellent bioindicator to evaluate soil quality (Souza and Fontanetti 2011;Souza et al 2014).…”
Section: Introductionmentioning
confidence: 99%